Review of medical microbiology and immunology - Levinson, Warren (New York : McGraw-Hill Medical, 2010)
"This book is a concise review of the medically important aspects of microbiology and immunology. It covers both the basic and clinical aspects of bacteriology, virology, mycology, parasitology, and immunology. Its two major aims are (1) to assist those who are preparing for the USMLE (National Boards) and (2) to provide students who are currently taking medical microbiology courses with a brief and up-to-date source of information. My goal is to provide the reader with an accurate source of clinically relevant information at a level appropriate for those beginning their medical education"--Provided by publisher.
Machine generated contents note: Preface -- Acknowledgements -- How to Use This Book -- I: Basic Bacteriology -- 1. Bacteria Compared With Other Organisms -- 2. Structure of Bacteria Cells -- 3. Growth -- 4. Genetics -- 5. Classification of Medically Important Bacteria -- 6. Normal Flora -- 7. Pathogenesis -- 8. Host Defenses -- 9. Laboratory Diagnosis -- 10. Antimicrobial Drugs: Mechanism of Action -- 11. Antimicrobial Drugs: Resistance -- 12. Bacterial Vaccines -- 13. Sterilization & Disinfection -- II: Clinical Bacteriology -- 14. Overview of the Major Pathogens & Introduction to Anaerobic Bacteria -- 15. Gram-Positive Cocci -- 16. Gram-Negative Cocci -- 17. Gram-Positive Rods -- 18. Gram-Negative Rods Related to the Enteric Tract -- 19. Gram-Negative Rods Related to the Respiratory Tract -- 20. Gram-Negative Rods Related to Animal Sources (Zoonotic Organisms) -- 21. Mycobacteria -- 22. Actinomycetes -- 23. Mycoplasmas -- 24. Spirochetes -- 25. Chlamydiae -- 26. Rickettsiae -- 27. Minor Bacterial Pathogens -- III: Basic Virology -- 28. Structure -- 29. Replication -- 30. Genetics & Gene Therapy -- 31. Classification of Medically Important Viruses -- 32. Pathogenesis -- 33. Host Defenses -- 34. Laboratory Diagnosis -- 35. Antiviral Drugs -- 36. Viral Vaccines -- PART IV: Clinical Virology -- 37. DNA Enveloped Viruses -- 38. DNA Nonenveloped Viruses -- 39. RNA Enveloped Viruses -- 40. RNA Nonenveloped Viruses -- 41. Hepatitis Viruses -- 42. Arboviruses -- 43. Tumor Viruses -- 44. Slow Virus & Prions -- 45. Human Immunodeficiency Virus -- 46. Minor Viral Pathogens -- V: Mycology -- 47. Basic Mycology -- 48. Cutaneous & Subcutaneous Mycoses -- 49. Systemic Mycoses -- 50. Opportunistic Mycoses -- VI: Parasitology -- 51. Intestinal & Urogenital Protozoa -- 52. Blood & Tissue Protozoa -- 53. Minor Protozoan Pathogens -- 54. Cestodes -- 55. Trematodes -- 56. Nematodes -- VII: Immunology -- 57. Immunity -- 58. Cellular Basis of the Immune Response -- 59. Antibodies -- 60. Humoral Immunity -- 61. Cell-Mediated Immunity -- 62. Major Histocompatibility Complex & Transportation -- 63. Complement -- 64. Antigen-Antobody Reactions in the Laboratory -- 65. Hypersensitivity (Allergy) -- 66. Tolerance & Autoimmune Disease -- 67. Tumor Immunity -- 68. Immunodeficiency -- VIII: Ectoparasites -- 69. Ectoparasites That Cause Human Disease -- IX: Brief Summaries of Medically Important Organisms -- Summaries of Medically Important Bacteria -- Summaries of Medically Important Viruses -- Summaries of Medically Important Fungi -- Summaries of Medically Important Parasites -- Summaries of Medically Important Ectoparasites -- X: Clinical Cases -- XI: Pearls for the USMLE -- XII: USMLE (National Board) Practice Questions -- Basic Bacteriology -- Clinical Bacteriology -- Basic Virology -- Clinical Virology -- Mycology -- Parasitology -- Immunology -- Extended Matching Questions -- Clinical Case Questions -- XIII: USMLE (National Board) Practice Examination -- Index.
"A Lange medical book."
Includes index.
Keywords: Medical microbiology -- Outlines, syllabi, etc; Clinical immunology -- Outlines, syllabi, etc; Microbiology -- Examination Questions; Microbiology -- Outlines; Allergy and Immunology -- Examination Questions; Allergy and Immunology -- Outlines; Immunologic Techniques -- Examination Questions; Immunologic Techniques -- Outlines